Pembuatan Aplikasi Berbasis Android sebagai Media Promosi Potensi Wisata di Kawasan Menoreh Samigaluh Kulon Progo - Muhammad Rifqi Al Fauzan; Sudiartono Sudiartono; Galih Setyawan; Tika Erna Putri; Imam Fakhrurrozi; Ronald Adrian; Atikah Surriani (Jurnal Pengabdian dan Pengembangan Masyarakat, 2018)
The aim of our community service program is to create promotion media of tourist attraction located in Menoreh, Samigaluh District, Kulon Progo Regency. Menoreh has a lot of not well-developed potential tourist attractions. There are not many information that we can obtain in internet about Menoreh attractions. This can be viewed from low number of visitors in Menoreh. Therefore a good promotion media is needed to solve the explained problem. Menoreh is a very potential area not only because of its natural resources but also because the government through the Ministry of Tourism establish Menoreh as a National Tourism Strategic Area (KSPN) Borobudur. There are many choices of promotional media that can be used, in this community service program we use Android-based application. Ministry of Communications and Information Republic of Indonesia in its official website predicts that by 2018 the number of active users of smartphones in Indonesia will exceed of 100 million users. Indonesia will be the country with the fourth largest smartphone active users in the world after China, India and the United States. From the that fact we can said that the promotion with smartphone-based application (by means of Android) is one of the most effective promotional methods today.